Aplikasi Herbisida Glifosat dan Paraquat pada Berbagai Dosis serta Pengaruhnya Terhadap Pertumbuhan Biduri (Calotropis Gigantean R. Br) - Gina Erida; Tjut Chamzurni (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Application of Different Dosage of Glyphosate and Paraquat Herbicides and Their Effect on the Growth of Milky Weed (Calotropis gigantean R. Br)ABSTRACT. The study on application the different dosages of glyphosate and paraquat herbicides and their effect on the growth milky weed (Calotropis gigantean) has been conducted at Experimental station, Faculty of Agriculture, Syiah Kuala University, Darussalam, Banda Aceh. The treatment were arranged in a completely randomized bloc design (CRD) manner with two factors. The first factor was the dosages of herbicides which were 0 kg a.i/ha, 0,4 kg a.i/ha, 0,8 kg a.i/ha, and 1,2 kg a.i/ha. The second one was the different herbicides which were glyphosate and paraquat. The result showed that the dosages of the 0,8 kg a.i/ha significantly increased the percentage of milky weed control, suppressed the height of milky weed 21 days of application (DAA), reduced the diameter of milky weed stem and decreased the dry weight of milky weed. The type of the herbicides and different dosages used interactively affected the percentage of milky weed control and the diameter of milky weed stem on 21 days of application (DAA). The paraquat herbicide applied with dosage of 1,2 kg a.i/ha significantly increased the percentage of milky weed control and suppressed the diameter of milky weed stem.